The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.9974
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Injury Patterns and Outcomes of Blunt Thoracic Trauma in Elderly Patients

Abstract: In the elderly population, trauma is a leading cause of utilization of healthcare, institutionalization, disability, and mortality. In this study, we will assess the injury patterns and the factors associated with the outcomes of blunt thoracic trauma in elderly individuals. Methods This prospective observational study was conducted in the Department of Thoracic Surgery, Jinnah Postgraduate Medical Center, Karachi, Pakistan, from September 2019 to April 2020. The study included patients of both genders aged 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Chronic lung disease has been reported previously as a predictor of poor in-hospital patient outcomes in patients with blunt chest wall trauma 8,33–35 . In this study, COPD was also a predictor of increased health care resource utilization in patients discharged directly home from the ED.…”
Section: Discussionsupporting
confidence: 50%
“…Chronic lung disease has been reported previously as a predictor of poor in-hospital patient outcomes in patients with blunt chest wall trauma 8,33–35 . In this study, COPD was also a predictor of increased health care resource utilization in patients discharged directly home from the ED.…”
Section: Discussionsupporting
confidence: 50%
“…Of these, 19 studies demonstrated a higher risk of mortality in patients aged 65 years or more when compared with patients aged less than 65 years 7 13–16 30–43. Other studies demonstrated that increased risk of mortality occurred in patients aged 50 years or more,17 55 years or more,44 45 60 years or more,46–50 70 years or more,51 80 years or more,52 and 90 years or more 53. A number of studies demonstrated an increasing risk of mortality per additional year of age5 54–56 and others with an additional decade 2 14 57.…”
Section: Resultsmentioning
confidence: 99%
“…There was however substantial heterogeneity across the studies with the independent variable investigated ranging from Elixhauser Comorbidity Count, Charlson Comorbidity Score, cardiopulmonary disease, cardiac disease and others. Eight studies investigated the risk factor cardiopulmonary disease with six reporting it as a significant risk factor2 52 53 56 76 77 and two reporting no significance 18 72. Congestive heart failure was a significant risk factor in six studies 2 17 33 53 56 72.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, thoracic trauma associated with lung contusion, more than two rib factors, hemopneumothorax, pneumonia, acute respiratory distress syndrome, and flail chest have contributed to lengthening geriatric patients' stay by more than 5 days duration. 18 Interestingly, thoracic trauma with AIS ≥3 in patients aged ≥65 years had .75 odds of mortality in our study. Over ¼ of the patients or 28% who had ICUBB in our cohort suffered head trauma.…”
Section: Discussionmentioning
confidence: 46%